Mendelian randomization study of sleep traits and risk of colorectal cancer - Dimopoulou, Olympia; Fuller, Harriett; Richmond, Rebecca C.; Bouras, Emmanouil; Hayes, Bryony; Dimou, Niki; Murphy, Neil; Brenner, Hermann; Gsur, Andrea; Le Marchand, Loic; Moreno, Victor; Pai, Rish K.; et al. (Scientific reports, 2025)
A potential association of endogenous circadian rhythm disruption with risk of cancer development has been suggested, however, epidemiological evidence for the association of sleep traits with colorectal cancer (CRC) is limited and often contradictory. Here we investigated whether genetically predicted chronotype, insomnia and sleep duration are associated with CRC risk in males, females and overall and according to CRC anatomical subsites using Mendelian randomization (MR). The two-sample inverse variance weighted (IVW) method was applied using summary-level data in up to 58,221 CRC cases and 67,694 controls and genome-wide association data of genetic variants for self-reported sleep traits. Secondary analyses using alternative instruments and sensitivity analyses assessing potential violations of MR assumptions were conducted. Genetically predicted morning preference was associated with 13% lower risk of CRC in men (ORIVW = 0.87, 95% CI = 0.78, 0.97, P = 0.01), but not in women or in both sexes combined. Τhis association remained consistent in some, but not all, sensitivity analyses and was very similar for colon and rectal cancer. There was no evidence of an association for any other sleep trait. Overall, this study provides little to no evidence of an association between genetically predicted sleep traits and CRC risk.